Răspuns :
[tex](3x + 5)(3x - 5) - {(2x + 5)}^{2} + 25x[/tex]
[tex]=(9 {x}^{2} - 25) - ( {4x}^{2} + 20x + 25) + 25x[/tex]
[tex] = 9 {x}^{2} - 25 - 4 {x}^{2} - 20x - 25 + 25x[/tex]
[tex] = 5 {x}^{2} + 5x - 50[/tex]
[tex]=(9 {x}^{2} - 25) - ( {4x}^{2} + 20x + 25) + 25x[/tex]
[tex] = 9 {x}^{2} - 25 - 4 {x}^{2} - 20x - 25 + 25x[/tex]
[tex] = 5 {x}^{2} + 5x - 50[/tex]
(a+b)(a-b)=a²-b²
(3x+5)(3x-5)=(3x)² - 5²=9x² - 25
(a+b)²=a²+2ab+b²
(2x+5)²=4x²+20x+25
9x² - 25 - (4x²+20x+25) +25x=
9x² - 25 - 4x²- 20x - 25 +25x=
5x² +5x - 50= 5(x²+x-10)
Sper că te-am ajutat!
(3x+5)(3x-5)=(3x)² - 5²=9x² - 25
(a+b)²=a²+2ab+b²
(2x+5)²=4x²+20x+25
9x² - 25 - (4x²+20x+25) +25x=
9x² - 25 - 4x²- 20x - 25 +25x=
5x² +5x - 50= 5(x²+x-10)
Sper că te-am ajutat!